The Role of Indigenous Knowledge Systems (IKS) in Improving Farm Productivity in Kainam Village, Mbulu District €“Tanzania - Hambati, Herbert (University of Dar es Salaam Library Journal, 2022)
This article aims to contribute to the current debate on the role of Indigenous Knowledge Systems (IKS) in arable land productivity. The study uses the Kainam Village ecosystem as a case study to describe the Iraqw community-based knowledge that supports their livelihoods. The study applied both qualitative and quantitative research methods to analyse the indigenous knowledge practices applied in arable land resources utilization. The conceptual framework around which most of the IKS analyses have hinged over time are narrated. It is conceived that IKS have demonstrated a synergetic relationship between land and the use to which it ' s put as they support hundreds of people in the village. The findings have revealed that Kainam people living in Mbulu District, have applied IKS in land classification and use, over centuries. IKS practices have sustained household yields and crops quality in the study area. Despite the small farm sizes, traditional tools and tilling methods, the households produce enough for their families and have surplus to assist relatives in far-away villages. This is due to the system of cultivating their farms throughout the year and the culturally in-built knowledge on land resources management, which has been historically accumulated, and used for survival and sustainability of household productivity in the village ecosystems. It is recommended that in order to sustain these best practices of IKS, it is important to integrate it into the curricula of the formal education system at all levels but particularly in primary education which is accessible to most rural Tanzanians.